Study of Methods and Development of Technological Scheme for Heat Removal from Rock Waste Dump - Saik, Pavlo (Trans Tech Publications, 2017)
The aim of this paper is to study the methods and develop technological scheme for thermal energy removal from coal mine rock waste dumps. The prospects of renewable energy sources development in Ukraine are analyzed. A number of available ways for using the sources of waste heat of mining enterprises, namely: outlet ventilation flow, mine water and other rock waste dumps, are investigated. The technological scheme of heat recovery from rock waste dump using heat pumps, which are component segments of the heat pump geosystem on the basis of borehole underground coal gasification, is developed.
Keywords: recovery energy source; heat pump; geosystem; underground coal gasification